Perceptions of family planning services and its key barriers among adolescents and young people in Eastern Nepal: A qualitative study. - Navin Bhatt (Public Library of Science (PLoS), 2021)
Introduction Family planning methods are used to promote safer sexual practices, reduce unintended pregnancies and unsafe abortion, and control population. Young people aged 15-24 years belong to a key reproductive age group. However, little is known about their engagement with the family planning services in Nepal. Our study aimed to identify the perceptions of and barriers to the use of family planning among youth in Nepal. Methods A qualitative explorative study was done among adolescents and young people aged 15-24 years from the Hattimuda village in eastern Nepal. Six focus group discussions and 25 in-depth interviews were conducted with both male and female participants in the community using a maximum variation sampling method. Data were analyzed using a thematic framework approach. Results Many individuals were aware that family planning measures postpone pregnancy. However, some young participants were not fully aware of the available family planning services. Some married couples who preferred 'birth spacing' received negative judgments from their family members for not starting a family. The perceived barriers to the use of family planning included lack of knowledge about family planning use, fear of side effects of modern family planning methods, lack of access/affordability due to familial and religious beliefs/myths/misconceptions. On an individual level, some couples' timid nature also negatively influenced the uptake of family planning measures. Conclusion Women predominantly take the responsibility for using family planning measures in male-dominated decision-making societies. Moreover, young men feel that the current family planning programs have very little space for men to engage even if they were willing to participate. Communication in the community and in between the couples seem to be influenced by the presence of strong societal and cultural norms and practices. These practices seem to affect family planning related teaching at schools as well. This research shows that both young men and women are keen on getting involved with initiatives and campaigns for supporting local governments in strengthening the family planning programs in Nepal.